When Da'wah Content Becomes a Trend: IRE Students’ Perspectives on the Phenomenon of Digital Da'wah on Campus - Nurul Azizah; Eti Rahmawati; Esha Aulia Septia Putri; Indri Dwina; Icha Kurniawati; Alfina Amalia Azizah (PT. Pusmedia Group Indonesia, 2025)
This study was conducted to examine the low level of active involvement among Islamic Religious Education (IRE) students in producing valid and responsible digital da'wah content, despite their religious background and access to social media. This study aims to explore the perspectives of Islamic Education (IE) students on the growing phenomenon of digital da'wah on social media. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation involving fifteen IRE students at the State Islamic University Raden Intan Lampung. The data analysis technique used was snowball sampling, which is effective for exploring IRE students' perspectives on their involvement in producing digital da'wah content. The findings reveal that digital da'wah through platforms such as TikTok, Instagram, and YouTube has a positive impact in strengthening students' religious understanding and behavior. Students appreciate the delivery of da'wah content that is creative, concise, and easy to understand. However, the study also identifies significant challenges, including the spread of unverified content, negative audience responses, and the low level of active participation of IRE students in producing da'wah content. This study indicates that students need to be further encouraged to enhance their skills and understanding of digital da'wah, so they can be more active and responsible in creating quality content that has a positive impact. This research recommends strengthening digital da'wah literacy, providing creative content training, and integrating the IRE curriculum with digital communication skills so that students can become not only consumers but also active and responsible producers of da'wah.